Antioxidant-Free Radical Scavenging of Some Euphorbiaceae Herbs - Sunarni, Titik; Leviana, Fransiska (Indonesian Journal of Cancer Chemoprevention, 2011)
In order to screen natural antioxidant, the research about antioxidant of some Euphobiaceae herbs,have been conducted.The air-dried herbs of Euphorbia heterophyllaL,PhyllanthusÃÂ  acidusÃÂ  (L.) Skeels, and PhyllanthusÃÂ  buxifoliusÃÂ  Muell Arg were extracted with metanol.The obtained extract was concentratedand then suspended to producen-hexane, ethyl acetat and aqueous fractions. Free radical scavenger activity against DPPH (1,1diphenyl2pycrylhydrazyl) measured by spectrophotometric method and the IC50 value was determined.The compounds of active fraction had been identified by TLC method. All of theherbs showed activity as DPPH scavenger.Among these herbs,Euphorbia heterophylla L. and Phyllanthus buxifolius Muell, Arg. exhibited a strong free radical scavenging of ethyl acetatfraction with IC50 value 5,883g/ml and 4,643g/ml.The result ofTLC by mobile phase n-buthanol acetic acid water(4:1:5) andacetic acid 15% showed flavonoid compound.